High-Loading Dose of Microencapsulated Gliclazide Formulation Exerted a Hypoglycaemic Effect on Type 1 Diabetic Rats and Incorporation of a Primary Deconjugated Bile Acid, Diminished the Hypoglycaemic Antidiabetic Effect - Golocorbin-Kon, S.; Calasan, J.; Milijasevic, B.; Vukmirovic, S.; Lalic-Popovic, M.; Mikov, M.; Al-Salami, Hani (Springer France, 2017)
Background and objective: Gliclazide is a drug commonly used in type 2 diabetes mellitus. Recently, gliclazide has shown desirable pharmacological effects such as immunoregulatory and anti-clotting effects, which suggests potential applications in type 1 diabetes mellitus (T1DM). Gliclazide has variable absorption after oral administration, and thus using targeted-delivery techniques, such as microencapsulation, may optimise gliclazide absorption and potential applications in T1DM. Bile acids such as cholic acid have shown microcapsule-stabilising and controlled-release effects, and thus their incorporation into gliclazide microcapsules may further optimise gliclazide release, absorption and antidiabetic effects. Accordingly, this study aimed to examine the hypoglycaemic effects of gliclazide microcapsules with and without cholic acid, in a rat model of T1DM. Methods: Thirty-five alloxan-induced T1DM rats were randomly divided into five equal groups and gavaged a single dose of empty microcapsules, gliclazide, gliclazide microcapsules, gliclazide-cholic acid or gliclazide-cholic acid microcapsules. Blood samples were collected over 10 h post-dose and analysed for blood glucose and gliclazide serum concentrations. Results: Gliclazide microcapsules exerted a hypoglycaemic effect in the diabetic rats, and cholic acid incorporation diminished the hypoglycaemic effects, which suggests the lack of synergistic effects between gliclazide and cholic acid. In addition, neither microencapsulation nor cholic acid incorporation optimised gliclazide absorption which suggests that hypoglycaemic effects of gliclazide are independent of its absorption and serum concentrations. This also suggests that hypoglycaemic effects of gliclazide may be associated with gut-metabolic activation rather than gut-targeted delivery and systemic absorption. Conclusion: Gliclazide microcapsules exerted hypoglycaemic effects in T1DM rats independent of insulin and thus may have potentials in treatment of T1DM.